Micro Push-Out Bond Strength of Resin Composite to Dentin in Primary Dentition Using Three Universal Adhesives with Different pH: An In Vitro Study - Regina María Del Río Carrillo; Pedro Molinero-Mourelle; Vicente Vera; Pablo Romero Villaba; Elizabeth Casañas; Manrique Fonseca; Vicente Vera-Gonzalez; María Rosa Mourelle-Martinez (Applied Sciences, 2021)
To evaluate the bond strength of different universal adhesives on deciduous tooth dentine and their relationship with the composition and potential of hydrogen (pH). Methods: An in vitro micro push-out test on 150 samples (n = 50) per group per adhesive, namely, Adhese Universal (ADH; Ivoclar Vivadent), Futurabond U (FUT; Voco GmbH) (Test), and Scotchbond Universal with pre-conditioning (SCO; 3M) (Control), to record bond strength (BS) and type of adhesive failure. Results: The results of the different adhesives (megapascals (MPa)) varied, showing no statistical significance. The corresponding averages are in MPa: ADH, 13.66 2.81; FUT, 14.48 2.88; SCO, 14.98 3.96. Additionally, the frequency of type of failure was as follows: mixed (60.7%), adhesive (27.3%), and cohesive (12%). Conclusions: SCO, with a pH of 2.7, showed greater resistance to fracture, while FUT, with a pH of 2.3 and no pre-conditioning, approached the same values, being a one-step adhesive. No relationship was found between failure and type of adhesive.